Thyroid autoimmunity and type 1 diabetes in children: screening datafrom Juvenile Diabetes Tuscany Regional Centre - Lenzi, L.; Mirri, S.; Generoso, M.; Guasti, et al., M. (Acta Biomedica Atenei Parmensis, 2009)
Background and Aims: The incidence of autoimmune thyroiditis in patients with type 1 diabetes mellitus (T1DM) is higher than in healthy population. The aim of this study is to investigate epidemiology and natural history of thyroid autoimmunity (AIT), thyroiditis diagnosis and need for therapy in paediatric patients with T1DM and to find the most suitable timing of AIT screening. Methods: T1DM patients (493 pts., 268 males and 225 females) treated in the Juvenile Diabetes Tuscany Regional Centre at Meyer’s Children Hospital were enrolled to determine TSH, fT4, thyroid autoantibodies levels and to undergo thyroid ultrasound. Anamnestic data about T1DM onset, AIT onset, time frame between T1DM and AIT onsets and the relationship between AIT and celiac disease (CD) were studied. Results: In the screened population 11.7% of patients presented with increased thyroid autoantibodies, and 63.6% of them showed positive thyroid ultrasound. AIT was significantly more frequent in females compared to males (p < 0.01). The mean age at AIT onset was 11,17 ± 3,29 years (range 4,99-20,30) and AIT onset before 12 yrs. of age was found in 54.5% of cases; 18.4% patients (all females) presented CD. The mean time between T1DM and AIT onset was 2,46 ± 3,41 years (range 0-13,41). The subgroup with increased thyroid autoantibodies was not statistically different from the whole population with regard to TDM1 duration and mean age at onset. Conclusions: AIT is frequently associated with T1DM (11.7%) regardless of age and duration of diabetes. We suggest a yearly screening for AIT after TDM1 onset, at every age.